Ponseti Casting vs. Soft Tissue Release for the Initial Treatment of Non-idiopathic Clubfoot - Abraham, Jonathan; Wall, Jon Cooper; Diab, Michel; Beaver, Cody (Frontiers in Surgery, 2021)
Purpose: Ponseti casting has universally been accepted as the gold standard for treatment of idiopathic clubfoot. Conversely, primary treatment for non-idiopathic clubfoot has not been established. The purpose of this study is to compare treatment outcomes following primary soft tissue release (STR) and Ponseti casting of non-idiopathic clubfoot. Methods: An IRB-approved retrospective study of patients treated for non-idiopathic clubfoot between 2005 and 2020 was conducted. Patients were included if they began treatment before the age of 2 and had at least 1 year of follow up. Patients were placed into either the STR group or Ponseti group and variables of interest were documented including reoccurrence of deformity, number of surgeries performed, type of surgeries performed, anesthesia time, and surgery time. Data was analyzed using Mann-Whitney U test for continuous variables. Results: A total of 33 children with 57 neuromuscular/syndromic clubfoot were identified of which 9 (15 feet) were treated with STR and 24 (42 feet) were treated with Ponseti casting. Average anesthesia and surgery time were found to be 291 and 179 min, respectively, for the STR group, and 113 and 67 min for the Ponseti group. The difference in operating time was determined to be significant (p = 0.02, p = 0.01). Patients treated with STR were found to have significantly more surgeries performed over the course of treatment than those treated with Ponseti casting (p = 0.001) with an average of 4.2 surgeries in the STR group and 1.5 surgeries in the Ponseti group. Extracapsular procedures were performed in 100% of the STR group and 97.6% of the Ponseti group (p = 0.55). Intracapsular procedures were performed in 100% of the STR group and 50% of the Ponseti group (p = 0.001). Conclusion: The Ponseti method should serve as the primary approach in the initial treatment of non-idiopathic clubfoot as it can reduce the risk of future invasive intracapsular surgery and shorten anesthesia and surgery times when surgical treatment is necessary. Level of Evidence: Level III retrospective case control study.